Peningkatan Kesadaran Hukum Lingkungan melalui Program Kampus Bersih Berbasis Partisipasi Civitas Akademika di Universitas Sunan Giri Surabaya - Atmari Atmari; Budi Handayani; Sustian Alfina; Dwi Sriwidadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This community service program aims to enhance environmental legal awareness through a participatory campus cleanliness initiative involving the academic community at Universitas Sunan Giri Surabaya. The primary issues addressed include limited understanding of environmental law, low participation in maintaining campus cleanliness, and the absence of sustained pro-environmental behavior. The program employed a participatory, educational, and practical approach, involving 50 students as participants. The activities were implemented through stages of environmental law education, waste management training, and direct action in the form of a campus clean-up program. The effectiveness of the program was measured using pre-test and post-test assessments, questionnaires, and field observations. The results indicate a significant improvement in participants’ knowledge, with average scores increasing from 62 to 86. In addition, there was a notable shift in attitudes, reflected in heightened awareness and concern for environmental cleanliness. Behavioral changes were also observed, particularly in the increased habit of proper waste disposal and active participation in maintaining campus cleanliness.The findings demonstrate that integrating environmental legal education with hands-on participation is an effective strategy for fostering comprehensive legal awareness. This program not only impacted individual participants but also contributed to the creation of a cleaner and more sustainable campus environment. Therefore, it has strong potential to be developed as a replicable model of community service in other higher education institutions